KAJIAN LEKSIKON MENTAL SUBJEK TUNGGAL LAKI-LAKI DAN PEREMPUAN MELALUI ASOSIASI KATA - Mardhiah, Ainun; Sastra, Gusdi; Usman, Fajri (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
This research aims to analyze the mental lexicon capacity of a male and a female subject using word association test. Distributional and identity methods were used in analyzing the data. This research employed Kent-Rosanoff word association test to measure and analyze the mental lexicon capacity and investigate the word class and conceptual areas. The findings of this research show that the mean of male and female mental lexicon capacity are significantly different, with male producing 11.26 words and female 13.39 words per stimulus. The female subject gave 213 more responses than the male subject. In this research, word class association forms uncovered striking similarities between the two sexes based on the response percentage hierarchy. The order from the highest number of word class association form to the lowest one is fairly the same: N-N ± 40%, A-N ± 20%, N-A ± 15%, N-V ± 8%, A-N ± 4%, V-N ± 3%, and A-V ± 2%. This research found that the male and female subjects' differences in mental lexicon capacity were due to psychological and social factors. Keywords: Mental lexicon capacity, male language, female language, word association